2019
DOI: 10.1111/jog.13878
|View full text |Cite
|
Sign up to set email alerts
|

‘Absent’ pulmonary valve with intact ventricular septum mimicking tricuspid valve atresia: Prenatal diagnosis and postnatal course

Abstract: Absent pulmonary valve syndrome is a rare congenital heart disease characterized by absent or rudimentary pulmonary valve leaflets and hypoplastic pulmonary annulus. The most common variant, associated with tetralogy of Fallot, implies dilatation of pulmonary branches and usually absent ductus arteriosus. Rarely, absent pulmonary valve occurs with intact ventricular septum: pulmonary branches are normally sized or mildly dilated and ductus arteriosus is usually patent. The rarest type is associated with intact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 13 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Monacci et al and Favilli et al have demonstrated that the spontaneous or surgical closure of the ductus arteriosus (DA), along with the progressive reduction in pulmonary vascular resistance, are crucial factors in enhancing pulmonary forward flow and enhancing both systolic and diastolic right ventricular functions. [2,5] Furthermore, the patient's haemodynamic and clinical conditions may improve even though the RV is dilated, due to good contractility. Immediate pulmonary valve surgery is unnecessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monacci et al and Favilli et al have demonstrated that the spontaneous or surgical closure of the ductus arteriosus (DA), along with the progressive reduction in pulmonary vascular resistance, are crucial factors in enhancing pulmonary forward flow and enhancing both systolic and diastolic right ventricular functions. [2,5] Furthermore, the patient's haemodynamic and clinical conditions may improve even though the RV is dilated, due to good contractility. Immediate pulmonary valve surgery is unnecessary.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, single-ventricle physiology condition is correlated with an underlying presence of tricus-pid atresia or stenosis, along with right ventricular hypoplasia. [1,2] APVS with an intact ventricular septum (IVS) or a small ventricular septum are rare subtypes of APVS and are associated with a high perinatal mortality. [3] Based on data from the foetal echocardiography database, the average gestational age for diagnosis can be as early as 21.5 weeks of gestation.…”
Section: Introductionmentioning
confidence: 99%
“…The high loss rate was related to pregnancy termination, fetal heart failure, respiratory disease, and chromosomal abnormalities [1,2]. The long-term following-up information was rarely analysed, whether with or without surgery [2][3][4]. Hence, the correct time for subsequent pulmonary valve surgery remains unknown [5].…”
Section: Discussionmentioning
confidence: 99%
“…Absent pulmonary valve syndrome (APVS) with an intact ventricular septum (IVS) or small ventricular septum is a rare type of APVS associated with high perinatal mortality in fetuses. Although APVS/IVS constitutes only 7.5% to 25% of the APVS cohort, most fetuses (80%) will not survive to birth without inotropic support or heart transplantation due to fetal heart failure, hydrops fetalis, extracardiac and chromosomal abnormities, and pregnancy termination [1][2][3][4]. A ductus arteriosus(DA) is usually present in APVS/IVS patients, and a large DA could result in bronchial compression leading to severe respiratory symptoms and signs of congestive heart failure early after birth [5].…”
Section: Introductionmentioning
confidence: 99%
“…While MPA and branch PA dilatation is a noted pathology, reports of airway compression by these dilated vessels is scarce. Literature search revealed analysis of this observation only in a subgroup of infants with prenatal diagnosis of absent PV syndrome; those with associated Tetralogy of Fallot (TOF) and with intact ventricular septum (which would later become IPVR) [4]. The observations from these rare reports (2/15 cases) are that presence of a ductus arteriosus to the MPA decompresses the branch PA and thereby reduce chances of airway compression.…”
Section: Discussionmentioning
confidence: 99%